Helping oneself, helping each other: Correlates of women’s participation in self-help groups - Arrieta, Alejandra; Jilani, Amir Hamza; Kumar, Neha; Quisumbing, Agnes R. (International Food Policy Research Institute, 2019)
Governments and development organizations worldwide are considering group-based platforms as alternatives to government- or market-based approaches for service delivery. This paper analyses the correlates of women’s membership in self-help groups (SHGs) using two datasets from India. Older women and those in villages without banks are more likely to join SHGs. Different findings across the two datasets highlight the drawbacks of using program evaluation data for guiding geographic targeting and placement of SHG programs. Our results emphasize the need to understand regional variations in membership and the unique characteristics of women, households, and villages when designing and targeting SHG platforms, particularly when using them for service delivery.